The Effect of Digital Marketing on Clothing Sales - Hanif, Hanif; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin; Rista, Nadia; Wahyuningsih, Sri (IJBLE Scientific Publications Community Inc., 2024)
This research aims to find out whether digital marketing has an effect on clothing sales at Tanah Abang Market Block A Floor 6, Central Jakarta. The method used in this research is quantitative with a survey approach. The population in this study were clothing shop owners at Tanah Abang Market, Block A, 6th Floor, Central Jakarta, totaling 403 shop owners with a sample size of 162. The results of the study showed that digital marketing had a significant influence on clothing sales at Tanah Abang Market, Block A, 6th Floor, Central Jakarta. which is shown from the results of the R Square coefficient of determination test of 0.220 so it can be concluded that 22% of digital marketing influences sales and the other 78% is influenced by other factors which the author did not examine in this research